Negotiating the future a labor perspective on American business - Bluestone, Barry 1944-; Bluestone, Irving (Basic Books, 1992)
It is no secret that corporate America is in trouble - as are labor unions - and a principal reason is our archaic system of labor-management relations that excludes labor from participating in, and sharing responsibility for, the growth and profitability of the enterprises for which they work. In a book sure to arouse controversy in both management and labor circles, the coauthor of the widely acclaimed The Deindustrialization of America and The Great U-Turn joins forces with his father, who has spent a lifetime as a union official, to propose a new Enterprise Compact under which labor becomes co-responsible with management for all strategic business decisions - pricing, investment, plant location, and more. The book describes innovative labor-management experiments, including the UAW-GM Saturn automobile project, to show that Enterprise Compacts are not impractical utopias, but promising means for making firms more efficient and profitable, improving employment security and the quality of working life, and restoring America's competitive edge. The authors argue that America will continue to lag behind its competitors as long as corporate decision making is blocked by an outworn, adversarial system of labor-management relations that no longer serves the interests of workers, stockholders, and the nation.
Keywords: Personnel - Participation à la gestion - États-Unis; Relations industrielles - États-Unis; Industrial relations -- United States; Management -- Employee participation -- United States; Mitbestimmung; Arbeitsbeziehungen; USA